Characterization of particle exposure in ferrochromium and stainless steel production. Issue 7 (2nd July 2016) - Järvelä, Merja; Huvinen, Markku; Viitanen, Anna-Kaisa; Kanerva, Tomi; Vanhala, Esa; Uitti, Jukka; Koivisto, Antti J.; Junttila, Sakari; Luukkonen, Ritva; Tuomi, Timo
ABSTRACT: This study describes workers' exposure to fine and ultrafine particles in the production chain of ferrochromium and stainless steel during sintering, ferrochromium smelting, stainless steel melting, and hot and cold rolling operations. Workers' personal exposure to inhalable dust was assessed using IOM sampler with a cellulose acetate filter (AAWP, diameter 25 mm; Millipore, Bedford, MA). Filter sampling methods were used to measure particle mass concentrations in fixed locations. Particle number concentrations and size distributions were examined using an SMPS+C sequential mobile particle sizer and counter (series 5.400, Grimm Aerosol Technik, Ainring, Germany), and a hand-held condensation particle counter (CPC, model 3007, TSI Incorporated, MN). The structure and elemental composition of particles were analyzed using TEM-EDXA (TEM: JEM-1220, JEOL, Tokyo, Japan; EDXA: Noran System Six, Thermo Fisher Scientific Inc., Madison, WI). Workers' personal exposure to inhalable dust averaged 1.87, 1.40, 2.34, 0.30, and 0.17 mg m −3 in sintering plant, ferrochromium smelter, stainless steel melting shop, hot rolling mill, and the cold rolling mill, respectively. Particle number concentrations measured using SMPS+C varied from 58 × 10 3 to 662 × 10 3 cm −3 in the production areas, whereas concentrations measured using SMPS+C and CPC3007 in control rooms ranged from 24 × 10 3 to 243 × 10 3 cm −3 and 5.1 × 10 3 to 97 × 10 3 cm −3, respectively. The elemental composition and the structure of particles in different production phases varied. In the cold-rolling mill non-process particles were abundant. In other sites, chromium and iron originating from ore and recycled steel scrap were the most common elements in the particles studied. Particle mass concentrations were at the same level as that reported earlier. However, particle number measurements showed a high amount of ultrafine particles, especially in sintering, alloy smelting and melting, and tapping operations. Particle number concentration and size distribution measurements provide important information regarding exposure to ultrafine particles, which cannot be seen in particle mass measurements.